Leilões de valor quase comum e o regime de partilha de produção brasileiro: uma abordagem teórica - Souza, Clara Costellini de (2012)
In this paper, we study by means of a theoretical approach the Brazilian production sharing regime for oil exploration approved in Law No 12.351. Some works in the almost common value auctions literature were also analysed. Furthermore, we develop a model for production sharing with asymmetric information to capture certain aspects of the Brazilian sharing model. Using numerical solutions, we discuss the bidders' strategies and their expected gains.